Respostas
respondido por:
4
x + 3y = 9 (-1)
2x + 3y = 6
-x - 3y = -9
2x + 3y = 6
============
x = -3
2x + 3y = 6
2.(-3) + 3y = 6
-6 + 3y = 6
3y = 6 + 6
3y = 12
y = 12/3
y = 4
s={ -3, 4 }
☆Espero ter ajudado!
2x + 3y = 6
-x - 3y = -9
2x + 3y = 6
============
x = -3
2x + 3y = 6
2.(-3) + 3y = 6
-6 + 3y = 6
3y = 6 + 6
3y = 12
y = 12/3
y = 4
s={ -3, 4 }
☆Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás